Safe third countries : extending the EU asylum and immigration policies to Central and Eastern Europe - Lavenex, Sandra (CEU Press, 1999)
"At a time when many transition countries are trying to enter the European Union, Lavenex highlights the willingness of Central and East European countries to adopt Western European policies aimed at fighting illegal immigration and reducing the numbers of asylum seekers as a political bargaining tool in exchange for future membership in the EU. She also argues that the emergent European refugee regime undermines the values of international refugee protection and diffuses states' responsibilities by establishing a system of negative redistribution for the handling of asylum claims."--Jacket